Analysis of AMDAL aspects on Bangkalan Red Land Goat Farms in the Perspective of Business Feasibility Study - Moh Aminulloh (Penerbit Hellow Pustaka, 2024)
Goat farms in Indonesia are currently developing very rapidly because many results can be obtained. Some of the results include the sale of parent, child and milk. Another addition is the result of processing goat manure (inthil) into organic fertilizer. Good feed provision and sufficient quantities need to be done to improve the quality of goats, milk and tillers produced. In order to continue to provide quality feed, knowledge is needed for making good quality fermented goat feed and can last a long time. Various kinds of processed goat milk can be produced such as pure milk packed in bottles or milk powder. Waste goat manure, both in the form of solid waste (inthil) or liquid waste (urine) if managed properly will provide economic added value. In addition, it is also necessary to assume about management and good marketing techniques to get maximum profits. The use of information technology (e-commerce) will be able to expand the marketing range of goat products in Indonesia.